Peran Pesantren dalam Pengembangan Ekonomi Islam - Rusmini (Fakultas Ekonomi dan Bisnis Islam, 2016)
The main problem in the development of the Islamic financial system is still their intent between the needs of industry and supply of human resources of the college. This study aims to analyze the potential and role of Islamic colleges and public colleges in the provision of human resources to accommodate the needs of the Islamic financial industry. Then, based on analysis of Islamic economic development, supported by a discourse with stakeholders, it was found that the differences in the learning system will provide perberdaan competence, among others through the curriculum standards, inconsistent use of terminology between Islam or Islamic study programs or courses. But it is unfortunate that graduates from a variety of different competencies are only a few that meet the needs of human resources in the industry.